The complete mitochondrial genome of Linguatula serrata (tongue worm) isolated from a dog and phylogenetic analysis - Tanian Naude; Sameer Pant; Mousa Tavassoli; Subir Sarker; Seyed Ali Ghorashi (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitogenome of Linguatula serrata isolated from nasal cavity of a dog was characterized for the first time. The total size of the circular mitogenome was 15,328 bp consisting of 37 genes including 13 protein coding genes, 22 tRNA genes, two rRNA genes and two control regions. Phylogenetic tree was constructed based on 17 closely related species and their genetic relationship with Linguatula serrata was analysed.